Ayurvedic Management of a Case of Central Retinal Vein Occlusion - Manjusree Radhakrishnan Parappurathu; Aravind Kumar; Krishnendu Sukumaran (Journal of Clinical and Diagnostic Research, 2019)
Central Retinal Vein Occlusion (CRVO) is classified based on aetiology into ischaemic and non-ischaemic varieties. Treatment modalities of CRVO include intra-vitreal anti-Vascular Endothelial Growth Factor (anti-VEGF) injections, pan-retinal LASER photocoagulation, and pars plana vitrectomy. The case of a 31-year-old female with a two-month history of blurring and fogginess of vision in her left eye (OS) and who were diagnosed previously with CRVO is presented here. Analysis of her symptoms using Ayurvedic diagnostics showed that she suffered from Timiraor blurring of vision. She underwent inpatient treatment in October 2014 and January 2015. Oral medicines such as Kashaya (decoctions), tablets, and Sattva (starch extract) were administered. External treatment included Pancakarma therapy and local therapies for the head and eye (Kriyakalpa). The Assessment was done using Distant Visual Acuity (DVA), posterior segment examination, and Optical Coherence Tomography (OCT), which showed improvement both at discharge and 2 subsequent follow-ups. This case illustrates that prompt and timely consultation and management brought about significant improvement in both her vision and well-being.